Impact of different chemotherapy regimens on intestinal mucosal injury assessed with bedside ultrasound: a study in 213 AML patients - Benedetti, Edoardo; Traverso, Ginevra; Pucci, Giulia; Morganti, Riccardo; Bramanti, Emilia; Lippolis, Piero; Susini, Maria Chiara; Mazzantini, Elisa; Giubbolini, Rachele; Mavilia, Fabrizio; Capochiani, Enrico; Neri, Emanuele; et al. (Frontiers in Oncology, 2023)
Neutropenic enterocolitis (NEC) is a life-threatening complication reported in patients with acute myeloid leukemia (AML) following chemotherapy (CHT).Intensive induction and consolidation CHT may damage intestinal mucosa leading to a NEC episode (NECe). NEC reported mortality may be up to 30-60%. Early US-guided bed-side diagnosis and prompt treatment may substantially improve the survival.An emerging worldwide concern is the intestinal colonization by multi-drug-resistant bacteria especially when patients are exposed to chemotherapy regimens potentially correlated to mucosal damage. In our study we prospectively enrolled all AML patients admitted in our leukemia unit to receive intensive induction and consolidation chemotherapy and experiencing chemotherapyinduced-neutropenia (CHTN). Overall, we enrolled N=213 patients from 2007 to March 2023. We recorded N=465 CHTN, and N=42 NECe (9.0% incidence). The aim of our study was to assess which chemotherapy regimens are more associated with NEC. We found that ALM1310, followed by 7+3 (daunorubicin), 7+3 (idarubicin), 5+3+3 (cytarabine, etoposide, idarubicin), and AML1310 (consolidation) were associated with a statistically higher incidence of NEC. We did not detect NEC episodes in patients treated with CPX-351, 5+2 (cytarabine, idarubicine), and high-dose cytarabine. Thus, we found that cytarabine could determine mucosal damage when associated with an anthracycline but not if delivered either alone or as dual-drug liposomal encapsulation of daunorubicin/cytarabine. We also describe NEC mortality, symptoms at diagnosis, intestinal sites involvement, and prognostic significance of bowel wall thickening.